2008
DOI: 10.3892/or.19.2.407
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation and sensitivity to antimetabolites in cancer cell lines

Abstract: Abstract. The prediction of the cellular direction of metabolic pathways toward either DNA synthesis or DNA methylation is crucial for determining the susceptibility of cancers to antimetabolites such as fluorouracil (5-FU). We genotyped the methylenetetrahydrofolate reductase (MTHFR) gene in NCI-60 cancer cell lines, and identified the methylation status of 24 tumor suppressor genes using methylation-specific multiplex ligation-dependent probe amplification. The susceptibility of the cancer cell lines to seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…31 Moreover, a recent in vitro study showed that cancer cell lines with methylated TIMP3 were more sensitive to 5-FU. 32 Aside from having high intracellular folate concentrations, another possible explanation for CIMP+ tumors showing better response to 5-FU is because of the silencing of critical genes. One candidate for this is the methylationinduced silencing of the dihydropyrimidine dehydrogenase gene (DPYD).…”
Section: Cimp+ and Gene Hypermethylationmentioning
confidence: 99%
“…31 Moreover, a recent in vitro study showed that cancer cell lines with methylated TIMP3 were more sensitive to 5-FU. 32 Aside from having high intracellular folate concentrations, another possible explanation for CIMP+ tumors showing better response to 5-FU is because of the silencing of critical genes. One candidate for this is the methylationinduced silencing of the dihydropyrimidine dehydrogenase gene (DPYD).…”
Section: Cimp+ and Gene Hypermethylationmentioning
confidence: 99%
“…Studies using these cells have successfully identified polymorphisms in candidate genes associated with drug response in vitro (Le Morvan et al, 2006;Jarjanazi et al, 2008;Puyo et al, 2008;Sasaki et al, 2008). Methylation of certain promoter CpG islands predicts toxicity to antimetabolites and alkylating agents in the NCI-60 lines (Shen et al, 2007;Sasaki et al, 2008).…”
Section: Nci-60 Cell-based Modelsmentioning
confidence: 99%
“…Studies using these cells have successfully identified polymorphisms in candidate genes associated with drug response in vitro (Le Morvan et al, 2006;Jarjanazi et al, 2008;Puyo et al, 2008;Sasaki et al, 2008). Methylation of certain promoter CpG islands predicts toxicity to antimetabolites and alkylating agents in the NCI-60 lines (Shen et al, 2007;Sasaki et al, 2008). Like HapMap LCLs, the NCI-60 panel has been important in examining the role of genetic variation in membrane transporters on sensitivity to chemotherapeutics (Huang et al, , 2005bSzaká cs et al, 2004;Liu et al, 2007a;Okabe et al, 2008;Pham et al, 2009).…”
Section: Nci-60 Cell-based Modelsmentioning
confidence: 99%
“…Studies using these cell lines have successfully identified polymorphisms in candidate genes associated with drug response in vitro (54-57) . Methylation of certain promoter CpG islands predicts toxicity to antimetabolites and alkylating agents in the NCI-60 lines (57, 58) . In addition, relationships between sensitivity to a panel of EGFR inhibitors and EGFR amplification, EGFR mutations and EGFR mRNA expression have been studied (59) .…”
Section: Gwas Studies In Preclinical Modelsmentioning
confidence: 99%